Effect of cataract surgery on cognitive function in elderly: Results of Fujiwara-kyo Eye Study. - Kimie Miyata; Tadanobu Yoshikawa; Masayuki Morikawa; Masashi Mine; Nozomi Okamoto; Norio Kurumatani; Nahoko Ogata (PLoS ONE, 2018)
To determine whether there is a significant association between prior cataract surgery and cognitive function in an elderly Japanese cohort.Nara Medical University, Nara, Japan.The Fujiwara-kyo Eye Study was a cross-sectional epidemiological study.The subjects were ≥ 68-years who lived in the Nara Prefecture and responded to recruitment notices. All of the subjects received comprehensive ophthalmological examinations, and answered questionnaires on their socio-demographic and medical history including prior cataract surgery. The association between prior cataract surgery and cognitive function was determined.A total of the 2764 subjects whose mean age was 76.3±4.8 years (±standard deviation) was studied. Of these, 668 individuals (24.2%) had undergone cataract surgery. Of these, 150 (5.4%) had dementia as determined by the Mini-Mental State Examination (MMSE) score ≤23, and 877 individuals (31.7%) had mild cognitive impairment (MCI; MMSE score 24-26). The subjects who had prior cataract surgery had significantly lower odds ratio (OR) of having MCI (OR = 0.78, 95% confidence interval; CI 0.64-0.96, P = 0.019) than those who had not had cataract surgery after adjusting for age, sex, body mass index, education, hypertension, diabetes, depression, and history of stroke. The OR was still lower when the visual acuity was also added to the adjusted factors (OR 0.79, 95% CI 0.64-0.97, P = 0.025). However, prior cataract surgery did not contribute significantly to the low OR for dementia.Cataract surgery may play a role in reducing the risk of developing MCI independently of visual acuity but not for dementia.